2015
DOI: 10.1097/01.hjh.0000469813.25726.de
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Adipose Tissue was Associated with Glomerular Hyperfiltration among Non- Diabetic and Normotensive Adults with a Normal Body Mass Index

Abstract: Glomerular hyperfiltration is recognized as an early marker of progressive kidney dysfunction in the obese population. This study aimed to identify the relationship between glomerular hyperfiltration and body fat distribution measured by computed tomography (CT) in healthy Korean adults. The study population included individuals aged 20-64 years who went a routine health check-up including an abdominal CT scan. We selected 4,378 individuals without diabetes and hypertension. Glomerular filtration rate was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…In our study, not only was SFA identified as a risk factor with a statistically significant difference, but VFA also tended to increase kidney events. There are also reports of an association between SFA and worse glomerular hyperfiltration in healthy males 15 . Our results support those of a study that reported an association between body fat and kidney events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, not only was SFA identified as a risk factor with a statistically significant difference, but VFA also tended to increase kidney events. There are also reports of an association between SFA and worse glomerular hyperfiltration in healthy males 15 . Our results support those of a study that reported an association between body fat and kidney events.…”
Section: Discussionsupporting
confidence: 91%
“…There are also reports of an association between SFA and worse glomerular hyperfiltration in healthy males. 15 Our results support those of a study that reported an association between body fat and kidney events. Based on these results, we considered that high body fat area in males aged <75 years with CKD could be a risk factor for kidney events.…”
Section: Discussionsupporting
confidence: 91%
“…GFR. Lee et al 24 demonstrated in adult and postmenopausal men and women that subcutaneous adipose tissue showed increased association with glomerular hyperfiltration. This association was explained by the increase in leptin levels that are released by subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…VFA and SFA were measured as previously described 19) . Briefly, the VFA and SFA were measured by diagnostic CT scanning at the umbilical crossing line 19 ) . CT scan images had already been performed for the assessment of ML.…”
Section: Evaluation Of Visceral Fat Area (Vfa) and Subcutaneous Fat Amentioning
confidence: 99%